BRIDGING THE GAP: A CONCEPTUAL MODEL FOR TRANSITIONING NF1 PATIENTS FROM PEDIATRIC TO ADULT CARE IN RESOURCE-LIMITED SETTINGS - Kuanova, Larissa; Zhienkulova , Gulzhanat; Eszhanova , Laura; Nugmanova, Jamilya (Interdisciplinary Approaches to Medicine, 2025)
Introduction:Neurofibromatosis type 1 (NF1) is a chronic autosomal dominant disorder requiring lifelong multidisciplinary oversight. International evidence shows that the transition from pediatric to adult care remains insufficiently standardized, despite the high risk of clinically significant complications during adolescence and early adulthood. Materials and Methods: A systematic search was performed across PubMed, Scopus and Web of Science (2015–2025) using the keywords “Neurofibromatosis type 1 in adults,” “transition care,” and “clinical pathway NF1.” English-language publications focusing on clinical and organizational aspects of transition were included.. Results: International recommendations emphasize early transition planning (starting at 14–16 years), risk-stratified follow-up, multidisciplinary surveillance, and structured transfer processes extending up to age 25. Key clinical risks during transition include tumor progression (e.g., plexiform neurofibromas, MPNST), neurocognitive impairments, vasculopathy, and skeletal deformities. Discussion: The absence of established NF1 transition pathways in Kazakhstan may contribute to delayed diagnosis of complications and fragmented care. International practices highlight the necessity of coordinated, multidisciplinary management supported by structured planning, patient education, and continuity between pediatric and adult services. Implementation feasibility is influenced by resource constraints and limited specialist availability. Conclusion: A stratified, structured transitional care model could improve early detection of NF1-related complications and strengthen continuity of care in Kazakhstan. Adoption of standardized transition pathways may enhance patient outcomes and support national rare disease strategies.